Factors influencing the acceptance of online teaching among dental students during COVID-19 crisis in India: A cross-sectional questionnaire-based survey - Mansi Atri; Sukhvinder Singh Oberoi; Nilima Sharma (Wolters Kluwer Medknow Publications, 2022)
Aim and Objectives: The present study assessed the perceived barriers as well as the preferences of the students toward the mode of education in the current scenario. Material and Methods: The study investigators developed a self-administered questionnaire using Google Forms® (Google LLC, Mountain View, CA) and were E-mailed to their respective E-mail ids and were informed telephonically about the survey. This survey was done among the BDS students of public health-care sector dental colleges in Delhi and the final data included 440 BDS dental students. Chi-square test was used to assess the association of the various factors among BDS students. Results: Higher response was obtained for Classroom Teaching for the 1st year students (65.6%) and Online Teaching for final year students (37.3%). The preference for online teaching over classroom teaching and understanding for the subject with your online classes was significantly better among final-year students (61.3%). The most common barrier experienced by the students was Network issue/poor range (52.5%) followed by understanding (17.0%) and excessive number of classes/Too long classes (10.2%). Conclusion: The present study showed that the 1st year dental students who just passed from the school had difficulty adapting to the Education via communication media. While the final year students were in a better position for adapting to the new system of learning.